2019
DOI: 10.1038/s41558-019-0514-9
|View full text |Cite
|
Sign up to set email alerts
|

Arctic greening and bird nest predation risk across tundra ecotones

Abstract: Alarming global-scale declines of birds numbers are occurring under changing climate 1 and species belonging to alpine and arctic tundra are particularly affected 2,3. Increased nest predation appears to be involved 4 , but the mechanisms linking predation to climate change remain to be shown. Here we test the prediction from food web theory that increased primary productivity (greening of tundra) in a warming arctic leads to higher nest predation risk in tundra ecosystems. Exploiting landscape-scale, spatial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 43 publications
3
28
0
Order By: Relevance
“…Finally, it should be noted that Ptarmigan (both Rock Ptarmigan and Willow Ptarmigan) are presently declining together with a host of other ground‐nesting bird species in alpine and Arctic ecosystems (Lehikoinen et al 2014, Lehikoinen et al 2019). This trend points toward drivers of change that are not exclusively linked to species‐specific traits or management, but rather to general changes in the ecosystem such a climate‐warming‐induced increased primary productivity (greening) and increased nest predation rates (Kubelka et al 2018, Ims et al 2019). This may also explain the declining trend in the Willow Ptarmigan population that was not accounted for by any of the predictors included in our model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, it should be noted that Ptarmigan (both Rock Ptarmigan and Willow Ptarmigan) are presently declining together with a host of other ground‐nesting bird species in alpine and Arctic ecosystems (Lehikoinen et al 2014, Lehikoinen et al 2019). This trend points toward drivers of change that are not exclusively linked to species‐specific traits or management, but rather to general changes in the ecosystem such a climate‐warming‐induced increased primary productivity (greening) and increased nest predation rates (Kubelka et al 2018, Ims et al 2019). This may also explain the declining trend in the Willow Ptarmigan population that was not accounted for by any of the predictors included in our model.…”
Section: Discussionmentioning
confidence: 99%
“…Considerations are further complicated by uncertainty about whether the population is in a transient state or at its natural attractor (Hastings et al 2018), that itself may be moving due to climate change. Furthermore, the community and continent‐wide decline in ground‐nesting birds (Lehikoinen et al 2014, Lehikoinen et al 2019) also urge for consideration of general drivers of change in alpine‐Arctic ecosystems (Ims et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…While we conclude that the red fox culling action had a clear positive effect by curbing the population decline seen in most places in Finnmark (Henden, Ims, et al., 2020), it did not lead to a population increase. A likely reason is that several other generalist predators like corvids exert increased impacts on alpine‐arctic birds in a warming climate (Ims et al., 2019). An important challenge for future studies is to obtain direct estimates of how populations of red fox and other members of arctic predator communities are impacted by climate change and management interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Increased nest predation from mesopredators has become a genuine concern regarding the conservation of many bird populations (Côté & Sutherland, 1997; Crooks & Soule, 1999; Kubelka et al., 2018; Marolla et al., 2019; Roos et al., 2018). Increased nest predation appears presently to be particularly acute in the Arctic (Ims et al., 2019; Kubelka et al., 2018), although no studies have so far been able to attribute this to any particular mesopredator species.…”
Section: Introductionmentioning
confidence: 99%
“…Climate change might have direct impact on some species, while others might be more affected by changes in carrion availability. Carrion availability from wild and domestic ungulates is to a great extent affected by management practices (Henden et al., 2014; Selås & Vik, 2006), possibly strengthening ecosystem disturbance caused by changes in climatic conditions (Ims et al., 2019). Management should take both factors into account, and we encourage further studies of the underlying mechanisms driving observed patterns of scavenger occurrence at baits, as these might be important to understand and predict ongoing ecosystem changes.…”
Section: Discussionmentioning
confidence: 99%